2009
DOI: 10.1002/uog.7334
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound pattern recognition by expert operators to identify borderline ovarian tumors: a study of diagnostic performance and interobserver agreement

Abstract: Objective To assess the accuracy and reproducibility of ultrasound 'pattern recognition' for the diagnosis of borderline ovarian tumors by asking experienced ultrasound operators to evaluate representative images of different types of adnexal tumor. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…No published mathematical model has yet replaced the effectiveness of this subjective evaluation, even in a subgroup of tumors qualified as "difficult to diagnose" 10 or for borderline tumors, 11,12 whose diagnosis may be more difficult than for invasive and benign tumors. 13 In our experience, the univariate analysis also showed that the clinician's judgment is the most discriminating factor in the diagnosis of malignancy, with an AUC of 0.795, sensitivity of 86%, and specificity of 73%. These numbers are nevertheless lower than published data, for which there are two possible reasons.…”
Section: Discussionmentioning
confidence: 64%
“…No published mathematical model has yet replaced the effectiveness of this subjective evaluation, even in a subgroup of tumors qualified as "difficult to diagnose" 10 or for borderline tumors, 11,12 whose diagnosis may be more difficult than for invasive and benign tumors. 13 In our experience, the univariate analysis also showed that the clinician's judgment is the most discriminating factor in the diagnosis of malignancy, with an AUC of 0.795, sensitivity of 86%, and specificity of 73%. These numbers are nevertheless lower than published data, for which there are two possible reasons.…”
Section: Discussionmentioning
confidence: 64%
“…The operators were also asked to provide the degree of confidence with which they made the diagnosis, confidence being classified into certain, probable and uncertain diagnosis. Full details of the image acquisition techniques, the histological classification and staging of tumors and the information provided to each of the examiners are given by Yazbek et al 9 The main outcome measure was the degree of confidence of the three experts in making the diagnosis of benign, borderline or invasive malignant ovarian tumor.…”
Section: Methodsmentioning
confidence: 99%
“…1, 2) had very similar sonographic features, a smaller diameter, fewer locules, higher numbers of papillary excrescences, and higher color scores inside solid components than mucinous BOTs of intestinal types [83]. They often manifest as unilocular-solid or multilocular-solid tumors with irregular and perfunded papillary projections without other signs of complexity, such as a solid pattern, irregular septae, and irregular inner walls due to tumor deposits in young women [81][82][83][84][85][86]. Their cyst fluid can be anechoic or have low-level or ground-glass echogenicity.…”
Section: Diagnosismentioning
confidence: 96%